Exploring the effect of complex patients on care delivery tasks. Issue 5 (8th June 2015) - Ozkaynak, Mustafa; Johnson, Sharon A.; Tulu, Bengisu; Donovan, Jennifer L.; Kanaan, Abir O.; Rose, Adam
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The needs of complex patients with chronic conditions can be unpredictable and can strain resources. Exploring how tasks vary for different patients, particularly those with complex needs, can yield insights about designing better processes in healthcare. The purpose of this paper is to explore the tasks required to manage complex patients in an anticoagulation therapy context. Design/methodology/approach – The authors analyzed interviews with 55 staff in six anticoagulation clinics using the Systems Engineering Initiative for Patient Safety (SEIPS) work system framework. The authors qualitatively described complex patients and their effects on care delivery. Findings – Data analysis highlighted how identifying complex patients and their effect on tasks and organization, and the interactions between them was important. Managing complex patients required similar tasks as non-complex patients, but with greater frequency or more intensity and several additional tasks. After complex patients and associated patient interaction and care tasks were identified, a work system perspective was applied to explore how such tasks are integrated within clinics and the resulting implications for resource allocation. Practical implications – The authors present a complex patient management framework to guide workflow design in specialty clinics, to better support high quality, effective, efficient and safe healthcare. Originality/value – The complex patient framework presented here, based on the SEIPS framework, suggests a more formal and integrated analysis be completed to provide better support for appropriate resource allocation and care coordination.